Fatores de risco e de proteção: um estudo de acompanhamento em pré-escolares com comportamentos agressivos - Picado, Juliana da Rocha (2006)
The interest of studding aggressive behaviors in preschoolers was justified because of the evidences related to these children s tendency to follow through disruptive behaviors pathways, marked by academic problems, grade retention and school drop-out, approach with antisocial peers and improvement of antisocial behaviors. One known protective factor that seems to minimize these risk factors and tend to reduce aggressive behaviors is the development of positive relationships between teacher and child. This research intend to study 11 preschoolers, with 7 years old, that had been pointed, when they were 5 years, as presenting aggressive behaviors in high frequency and intensity. The objectives were 1) to characterize this group in aggressive behaviors, other behavior problems, academic skills and school adjustment; 2) to verify the stability of these behaviors along two years; 3) Identify possible risk factors in which these children are exposed; and 4) evaluate if the relationship between teachers and students contains protective elements. The instruments used with teachers were: Teacher's Report Form TRF, which evaluate externalizing and internalizing problems; the Academic Skills and School Adjustment Interview, and the Teacher's Relationship Interview. The mothers answered the Adverse Events Scale as well as an interview about educative practices. Results indicate that 63.6% of the children remain aggressiveness indications according to current teachers, and the other children also have problems as hyperactivity, insecurity, and low self-esteem. TRF indicates the presence of problems in all of the studied children. Ten of eleven cases (90.9%) present externalizing problems, two (18.1%) internalizing problems, and nine of them (81.8%) indications for total problems. In the individual scales of TRF, five children received clinical indication for aggressive behaviors. The academic skills of 54.5% of the children were considered satisfactory, while school adjustment were instable in all of the cases. It is verified that all children are exposed to many risk factors, in special those related to financial problems and family context, through educational practices used. The results of teacher-child relationships pointed that two teachers (18.1%) were considerate able to represent protective factor to their students. Both present high sense of discipline, represent secure base for their students, have empathy, are able to talk about negative events related to the student or to the relationship, feel effective in teaching and also feel capable to reach and to modify student's behaviors as well as demonstrate positive feelings in relation to them. Four teachers (36.3%) showed less presence of these characteristics, and other five (45.4%) seems not to be able to represent protective factors to theirs students. All of these children are exposed to risk factors, and the majority of them do not seem to have protective factors enough to minimize the risk effects in their lives. Possible aggressive pathways to be followed by these children are discussed. The prevention and reduction of aggressive behaviors in preschoolers seems to be the most appropriate alternative to interrupt the evolution of early conduct problems. It is emphasized the needed to develop special competences in teachers, making them able to manage with aggressive behaviors or other behaviors problems, becoming protective factors to those children.